Gender Justice in Tudang Sipulung: An Ecofeminist–Maqāṣid al-Sharīʿah Reading of Inheritance in Bugis Bone, Indonesia - Asni, Asni; Tarmizi, Tarmizi; Kiljamilawati, Kiljamilawati; Patimah, Patimah; Kartini, Kartini; Ahmad, Md. Yazid (IAIN Manado, 2025)
This article examines Tudang Sipulung, a traditional deliberative forum within the Bugis community of Bone Regency, South Sulawesi, as a culturally embedded mechanism for the distribution of inheritance. Using an ecofeminist perspective alongside the framework of maqāṣid al-sharīʿah, the study employs an empirical legal approach combined with legal-anthropological analysis. Data were collected through semi-structured interviews with religious leaders, local government officials, and heirs, supported by field observations and an examination of religious court decisions and village archival records. The findings show that women actively participate in inheritance deliberations and play a significant role in maintaining both family harmony and environmental sustainability. Their involvement reflects a close relationship between women’s economic responsibilities, household livelihoods, and ecological awareness. The practice of Tudang Sipulung demonstrates the protection of wealth (ḥifẓ al-māl) through negotiated and equitable distribution; the protection of lineage (ḥifẓ al-nasl) by reducing intrafamily conflict; and the protection of life (ḥifẓ al-nafs) by discouraging excessive accumulation and social tension. Conceptually, this study contributes to Islamic legal scholarship by reading customary inheritance practices through the combined lenses of ecofeminism and maqāṣid al-sharīʿah. In practice, it offers a gender-sensitive, environmentally grounded mediation model that may inform the resolution of inheritance disputes in pluralistic social settings.